Two-phase slug flow measurement using ultra-sonic techniques in combination with T-Y junctions - Khalifa, K. M. (Cranfield University, 2010)
The accurate measurement of multiphase flows of oil/water/gas is a critical element of oil exploration and production. Thus, over the last three decades; the development and deployment of in-line multiphase flow metering systems has been a major focus worldwide. Accurate measurement of multiphase flow in the oil and gas industry is difficult because there is a wide range of flow regimes and multiphase meters do not generally perform well under the intermittent slug flow conditions which commonly occur in oil production. This thesis investigates the use of Doppler and cross-correlation ultrasonic measurements made in different high gas void fraction flow, partially separated liquid and gas flows, and homogeneous flow and raw slug flow, to assess the accuracy of measurement in these regimes. This approach has been tested on water/air flows in a 50mm diameter pipe facility. The system employs a partial gas/liquid separation and homogenisation using a T-Y junction configuration. A combination of ultrasonic measurement techniques was used to measure flow velocities and conductivity rings to measure the gas fraction. In the partially separated regime, ultrasonic cross-correlation and conductivity rings are used to measure the liquid flow-rate. In the homogeneous flow, a clamp-on ultrasonic Doppler meter is used to measure the homogeneous velocity and combined with conductivity ring measurements to provide measurement of the liquid and gas flow-rates. The slug flow regime measurements employ the raw Doppler shift data from the ultrasonic Doppler flowmeter, together with the slug flow closure equation and combined with gas fraction obtained by conductivity rings, to determine the liquid and gas flow-rates. Measurements were made with liquid velocities from 1.0m/s to 2.0m/s with gas void fractions up to 60%. Using these techniques the accuracies of the liquid flow-rate measurement in the partially separated, homogeneous and slug regimes were 10%, 10% and 15% respectively. The accuracy of the gas flow-rate in both the homogeneous and raw slug regimes was 10%. The method offers the possibility of further improvement in the accuracy by combining measurement from different regimes.
Keywords: T-Y junction; ultrasonic cross-correlation; ultrasonic Doppler flowmeter; multiphase flow; conductivity ring; signal analysi